Platelets and platelet adhesion support angiogenesis while preventing excessive hemorrhage - Kisucka, Janka (National Academy of Sciences, 2006)
Platelets contain both pro- and antiangiogenic factors, but their regulatory role in angiogenesis is poorly understood. Although previous studies showed that platelets stimulate angiogenesis in vitro, the role of platelets in angiogenesis in vivo is largely uncharacterized. To address this topic, we used two in vivo approaches, the cornea micropocket assay and the Matrigel model, in four animal models: thrombocytopenic, Lyst(bg) (platelet storage pool deficiency), glycoprotein (GP) Ibα/IL4R transgenic (lacking extracellular GPIbα, the receptor for von Willebrand factor as well as other adhesive and procoagulant proteins), and FcγR(–/–) (lacking functional GPVI, the collagen receptor) mice. Adult mice were rendered thrombocytopenic by i.p. administration of an antiplatelet antibody. The number of growing vessels in the thrombocytopenic mice was lower in the cornea assay, and they showed significantly increased appearance of hemorrhage compared with mice treated with control IgG. The thrombocytopenic mice also showed more protein leakage and developed hematomas in the Matrigel model. GPIbα/IL4R transgenic mice presented increased hemorrhage in both assays, but it was less severe than in the platelet-depleted mice. FcγR(–/–) and Lyst(bg) mice showed no defect in experimental angiogenesis. Intravital microscopy revealed a >3-fold increase in platelet adhesion to angiogenic vessels of Matrigel compared with mature quiescent skin vessels. Our results suggest that the presence of platelets not only stimulates angiogenic vessel growth but also plays a critical role in preventing hemorrhage from the angiogenic vessels. The adhesion function of platelets, as mediated by GPIbα, significantly contributes to the process.